Три мушкетера: роман / Александр Дюма - Дюма Александр (Школьная библиотека, 1990)
Экземпляры: ф.14 (1991) / Инвентарный номер: 33117 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Д 96 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44